ISLAM, TOLERANSI DAN KERUKUNAN UMAT ANTAR BERAGAMA - Usman, Ilham (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This study was driven by a series of events that showed the religious behavior of a few people in Indonesia who are less tolerant. This article presents the results of research on the Islamic view of tolerance and the contribution of Islam to the treatment of religious people in Indonesia. This study uses library research. The results of the study found that Islam used the Arabic language of Tasamuh to accommodate the attitude of tolerance of its people toward other religions, and the roots of classical Islamic tolerance can be found in the thought of Murji’ah, Qadariyah, and Ibn Rusyd Philosophy. The Prophet (peace and blessings of Allah be upon him) said: